2021
DOI: 10.1051/0004-6361/202140688
|View full text |Cite
|
Sign up to set email alerts
|

An ultra-short-period transiting super-Earth orbiting the M3 dwarf TOI-1685

Abstract: Dynamical histories of planetary systems, as well as the atmospheric evolution of highly irradiated planets, can be studied by characterizing the ultra-short-period planet population, which the TESS mission is particularly well suited to discover. Here, we report on the follow-up of a transit signal detected in the TESS sector 19 photometric time series of the M3.0 V star TOI-1685 (2MASS J04342248+4302148). We confirm the planetary nature of the transit signal, which has a period of Pb = 0.6691403−0.0000021+0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 103 publications
0
20
0
1
Order By: Relevance
“…Their resulting RV semiamplitude is discrepant from ours at 5σ as they measure a larger RV semiamplitude of =  K 10.8 1.0 m s −1 and show that TOI-1634 b is likely consistent with an Earth-like composition. Similarly, the second USP planet presented in Hirano et al (2021;TOI-1685 b) was also found to be consistent with an Earth-like composition, whereas this planet was previously shown to be underdense relative to an Earth-like composition using CARMENES RV measurements (Bluhm et al 2021). The similar analyses conducted in this work, in Hirano et al (2021), and in Bluhm et al (2021) suggest that the differences in the IRD results compared to HARPS-N for TOI-1634 b and compared to CARMENES for TOI-1685 b are derived from the IRD data and not from issues with any one group's analysis.…”
Section: An Independent Analysis Of the Toi-1634 Systemmentioning
confidence: 52%
See 3 more Smart Citations
“…Their resulting RV semiamplitude is discrepant from ours at 5σ as they measure a larger RV semiamplitude of =  K 10.8 1.0 m s −1 and show that TOI-1634 b is likely consistent with an Earth-like composition. Similarly, the second USP planet presented in Hirano et al (2021;TOI-1685 b) was also found to be consistent with an Earth-like composition, whereas this planet was previously shown to be underdense relative to an Earth-like composition using CARMENES RV measurements (Bluhm et al 2021). The similar analyses conducted in this work, in Hirano et al (2021), and in Bluhm et al (2021) suggest that the differences in the IRD results compared to HARPS-N for TOI-1634 b and compared to CARMENES for TOI-1685 b are derived from the IRD data and not from issues with any one group's analysis.…”
Section: An Independent Analysis Of the Toi-1634 Systemmentioning
confidence: 52%
“…Similarly, the second USP planet presented in Hirano et al (2021;TOI-1685 b) was also found to be consistent with an Earth-like composition, whereas this planet was previously shown to be underdense relative to an Earth-like composition using CARMENES RV measurements (Bluhm et al 2021). The similar analyses conducted in this work, in Hirano et al (2021), and in Bluhm et al (2021) suggest that the differences in the IRD results compared to HARPS-N for TOI-1634 b and compared to CARMENES for TOI-1685 b are derived from the IRD data and not from issues with any one group's analysis. The exact cause of these discrepancies is currently unknown, and their resolution is left as a future exercise.…”
Section: An Independent Analysis Of the Toi-1634 Systemmentioning
confidence: 52%
See 2 more Smart Citations
“…We found the fluctuations are too small to be observable for an Earth-sized planet like Proxima Centauri b, but as QBOlike phenomena have also been detected on Jupiter and Saturn in the solar system (Showman et al 2019;Orton et al 1991;Leovy et al 1991), a LASO could potentially occur on a larger planet with greater potential for observation. This could be particularly important for short-period, potentially tidally locked, super-Earth or mini-Neptune-type planets detected by missions such as the Transiting Exoplanet Survey Satellite (see Bluhm et al (2021) for a recent example)…”
Section: Atmospheric Water Vapour Oscillationsmentioning
confidence: 99%